The Tumbling Turner sisters - Fay, Juliette (Gallery Books, 2016)
"In 1919, the four Turner sisters and their parents are barely scraping along. Their father is a low-paid boot stitcher in Johnson City, NY, and the Turners are always one paycheck away from eviction. When their father's hand is crushed and he's forced to quit, their domineering mother decides that the vaudeville stage is their best--and only--chance for salvation. With everything at stake, the Tumbling Turners take to the road and the four young women, teenagers Gert, Winnie, and Kit, and Nell, a 22-year-old new mother and recent widow of the Great War, are soon immersed in the tumultuous world of American Vaudeville on a nine-city tour that will make or break them. Swindlers and ne'er-do-wells await in abundance, but so does kindness, and just maybe a chance at love."--